PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM DAN COURSE REVIEW HORAY BERBASIS LESSON STUDY UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS XI IPS 2 MAN KOTA BATU - Arfiyanti Agustiningrum (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2017)
This research aims to increase the activity and student learning outcomes in Social Eleventh Graders at 2 MAN Batu by implementing Flipped Classroom and Course Review Horray (CRH) learning model based lesson study. This research consisted of two cycles. Data were collected through documentation, observation, field notes, and tests. Qualitative descriptive tehnique was employed for analyzing the data. The results of student learning activities in the first cycle was 58 and the second cycle the stucdent learning activities value increased to 72. The research result of students learning outcomes in the first cycle was 75,00% and the second cycle increased to 89,29%. DOI: https://dx.doi.org/10.17977/UM014v10i22017p126